Exploring the impact of a complex intervention for women with depression in contexts of adversity: A pilot feasibility study of COURRAGE-plus in South Africa. (June 2022) - Burgess, Rochelle A; Jeske, Niklas; Rasool, Shahana; Ahmad, Ayesha; Kydd, Anna; Ncube Mlilo, Ncazelo
Background: Depression is a leading cause of disease burden worldwide but is often undertreated in low- and middle-income countries. Reasons behind the treatment gap vary, but many highlight a lack of interventions which speak to the socio-economic and structural realties that are associated to mental health problems in many settings, including South Africa. The COURRAGE-PLUS intervention responds to this gap, by combining a collective narrative therapy (9 weeks) intervention, with a social intervention promoting group-led practical action against structural determinants of poor mental health (4 weeks), for a total of 13 sessions. The overall aim is to promote mental health, while empowering communities to acknowledge, and respond in locally meaningful ways to social adversity linked to development of mental distress. Aim: To pilot and evaluate the effectiveness of a complex intervention – COURRAGE-PLUS on symptoms of depression as assessed by the Patient Health Questionnaire (PHQ-9) among a sample of women facing contexts of adversity in Gauteng, South Africa. Methods: PHQ-9 scores were assessed at baseline, post collective narrative therapy (midline), and post social intervention (endline). Median scores and corresponding interquartile ranges were computed for all time points. Differences in scores between time points were tested with a non-parametric Friedman test. The impact across symptom severities was compared descriptively to identify potential differences in impact across categories of symptom severity within our sample. Results: Participants' ( n  = 47) median depression score at baseline was 11 (IQR = 7) and reduced to 4 at midline (IQR = 7) to 0 at endline (IQR = 2.5). The Friedman test showed a statistically significant difference between depression scores across time points, χ 2 (2) = 49.29, p  < .001. Median depression scores were reduced to 0 or 1 Post-Intervention across all four severity groups. Conclusions: COURRAGE-PLUS was highly effective at reducing symptoms of depression across the spectrum of severities in this sample of women facing adversity, in Gauteng, South Africa. Findings supports the need for larger trials to investigate collective narrative storytelling and social interventions as community-based interventions for populations experiencing adversity and mental distress.